The photographer's guide to Lightroom : learn industry-standard best practices and techniques to get the best out of the latest version of Lightroom Classic /: learn industry-standard best practices and techniques to get the best out of the latest version of Lightroom Classic. (2022) - Lewandowski, Marcin
No abstract available